2022
DOI: 10.3390/genes13061092
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression Analysis Reveals Differential Expression of Homologous Genes Associated with Specific Terpenoid Biosynthesis in Rehmannia glutinosa

Abstract: Terpenoids are naturally occurring compounds involved in respiration, photosynthesis, membrane fluidity, and pathogen interactions and are classified according to the structure of their carbon skeleton. Although most terpenoids possess pharmacological activity, knowledge about terpenoid metabolism in medicinal plants is insufficient. Rehmannia glutinosa (R. glutinosa) is a traditional herb that is widely used in East Asia and has been reported to contain various terpenoids. In this study, we performed a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…In addition, metabolic pathways such as starch, fructose, carbohydrate transport, sucrose, and galactose were activated in the roots ( Figures 6A, B and Supplementary Tables 15, 16 ). Similar results were also confirmed in other comparative combinations ( Supplementary Tables 17-20 ), suggesting that the roots of A. membranaceus play a vital role in the synthesis of carbohydrates and pharmacological substances, potentially offering significant benefits for human health ( Kang et al., 2021 ; Kang et al., 2022 ). The raw information of GO and KEGG based on DEGs was presented in Supplementary Tables 21-23 .…”
Section: Resultssupporting
confidence: 81%
“…In addition, metabolic pathways such as starch, fructose, carbohydrate transport, sucrose, and galactose were activated in the roots ( Figures 6A, B and Supplementary Tables 15, 16 ). Similar results were also confirmed in other comparative combinations ( Supplementary Tables 17-20 ), suggesting that the roots of A. membranaceus play a vital role in the synthesis of carbohydrates and pharmacological substances, potentially offering significant benefits for human health ( Kang et al., 2021 ; Kang et al., 2022 ). The raw information of GO and KEGG based on DEGs was presented in Supplementary Tables 21-23 .…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, farnesyl diphosphate synthase (FPS), SS, and SE have been implicated in regulating triterpenoid saponin synthesis. 30,31 In the present study, FPS and SS were expressed higher in 1-year-old seedlings. Previous research on birch saponins has shown that heterologous expression of FPS in yeast increased squalene expression, resulting in higher production of triterpene saponins, such as bircholic acid, oleanolic acid, and betulinic acid.…”
Section: Resultssupporting
confidence: 59%
“…The terpenoids of primary metabolism have been shown to play important roles in sustaining life activities [ 7 ]. For example, carotenoids participate in photosynthetic reactions as photosynthetic pigments [ 8 , 9 ]; gibberellins, abscisic acid, and cytokinins participate as regulators of plant growth and development [ 10 ]; phytosterols participate as influencing factors of membrane structure and function [ 11 , 12 ]; ubiquinone and plastoquinone side chains function as electron carriers; and polyphenols participate in protein glycosylation [ 13 ]. However, terpenoids in most plants exist in the form of secondary metabolites, which do not directly participate in plant growth and development, but have certain physiological functions, such as plant defense responses [ 14 ], pharmacological compounds [ 15 ], and fragrance volatilization [ 4 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%